Features of successful academic hospitalist programs: Insights from the SCHOLAR (SuCcessful HOspitaLists in academics and research) project. Issue 10 (18th May 2016) - Seymann, Gregory B.; Southern, William; Burger, Alfred; Brotman, Daniel J.; Chakraborti, Chayan; Harrison, Rebecca; Parekh, Vikas; Sharpe, Bradley A.; Pile, James; Hunt, Daniel; Leykum, Luci K.
Abstract : BACKGROUND: As clinical demands increase, understanding the features that allow academic hospital medicine programs (AHPs) to thrive has become increasingly important. OBJECTIVE: To develop and validate a quantifiable definition of academic success for AHPs. METHODS: A working group of academic hospitalists was formed. The group identified grant funding, academic promotion, and scholarship as key domains reflective of success, and specific metrics and approaches to assess these domains were developed. Self‐reported data on funding and promotion were available from a preexisting survey of AHP leaders, including total funding/group, funding/full‐time equivalent (FTE), and number of faculty at each academic rank. Scholarship was defined in terms of research abstracts presented over a 2‐year period. Lists of top performers in each of the 3 domains were constructed. Programs appearing on at least 1 list (the SCHOLAR cohort [SuCcessful HOspitaLists in Academics and Research]) were examined. We compared grant funding and proportion of promoted faculty within the SCHOLAR cohort to a sample of other AHPs identified in the preexisting survey. RESULTS: Seventeen SCHOLAR programs were identified, with a mean age of 13.2 years (range, 6–18 years) and mean size of 36 faculty (range, 18–95). The mean total grant funding/program was $4 million (range, $0–$15 million), with mean funding/FTE of $364, 000 (range, $0–$1.4 million); both were significantly higher than the comparison sample. The majority of SCHOLAR faculty (82%) were junior, a lower percentage than the comparison sample. The mean number of research abstracts presented over 2 years was 10.8 (range, 9–23). DISCUSSION: Our approach effectively identified a subset of successful AHPs. Despite the relative maturity and large size of the programs in the SCHOLAR cohort, they were comprised of relatively few senior faculty members and varied widely in the quantity of funded research and scholarship. Journal of Hospital Medicine 2016;11:708–713. © 2016 Society of Hospital Medicine